DETENTION AS A MEASURE OF PROCEDURAL COERCION IN CRIMINAL PROCEEDINGS (Journal of actual problems of jurisprudence, 2018)
The article discusses the features of the detention of a suspect in a criminal offense, provided the criminal procedural legislation of the Republic of Kazakhstan. Identify the main features, objectives and order of detention as a measure of procedural coercion. The problematic issues of the legislation on the terms of detention, the limits of the use of force during detention, and the grounds for recognizing detention as unlawful and unreasonable are covered. Suggestions are made to improve the norms of the Code of Criminal Procedure of the Republic of Kazakhstan in order to properly ensure the rights of the individual during detention. The relevance of this article is due to the fact that in criminal procedure science there are problems that relate to ensuring the rights of the individual in the process of procedural actions using the means of criminal procedural coercion, since in this case the constitutional rights and freedoms of participants in criminal proceedings are more affected. The purpose of this article is to consider the procedure for detaining a suspect as a procedural coercion measure applied by the inquiry body, investigator, interrogator or prosecutor for a period not exceeding 72 hours from the moment of actual detention of a person on suspicion of committing a crime. The essence of this measure is the short-term deprivation of liberty of a person suspected of committing a crime in order to ascertain his identity, involvement in a crime and to decide on the application of a preventive measure to him – usually detention. The author considers that the detention of a suspect is a short-term restriction of freedom. The grounds for carrying out this action, entered in the protocol, simultaneously act as factual data, circumstances having evidentiary value. But, the purpose of the detention is to deprive a person suspected of committing a criminal offense, to have the opportunity to exert an undue influence on the investigation process, to resist the establishment of truth in a criminal case, to hide from the bodies of inquiry, investigation and judicial bodies, to continue unlawful activities. Thus, it follows that it is necessary in law enforcement work practice factors unjustified detention should be excluded and money, unlawful criminal responsibility.Key words: detention, criminal prosecution, coercive procedural measure, authorized persons, period of detention, procedure for the detention, procedural prosecutor, criminal process